SENI LUKIS MEDIA TERAPI ANAK SINDROM AUTISTIK DI UPTD PUSAT LAYANAN DISABILITAS KOTA DENPASAR - I.G.P.A Mirah Rahmawati (Widyadari, 2025)
Autism is a type of developmental disorder in children and has become a social humanitarian phenomenon in today's modern society. Another social humanitarian phenomenon is the community's general lack of knowledge about autism, which leads to discrimination and even rejection of individuals with autism. Art therapy is expected to serve as an alternative in the field of health therapy. Artistic activities can be a simple approach for improving the behavior of children with autism, helping them become calmer and improving their concentration.The problems addressed in this study are divided into three main points, The implementation of elements of visual art as a psychological therapy medium for children with autism syndrome at the UPTD Disability Service Center in Denpasar. The challenges faced in applying visual art as a psychological therapy medium for children with autism syndrome at the UPTD Disability Service Center in Denpasar. The impact of visual art as a psychological therapy medium for children with autism syndrome at the UPTD Disability Service Center in Denpasar.The theories used to address these three issues are psychoanalytic theory, the theory of aesthetic unconsciousness, and the theory of expression. This research is divided into three stages: (1) the data collection stage, which uses observation and interview methods, along with note-taking and analysis techniques; (2) the data analysis stage, where data is analyzed; and (3) the presentation of the data analysis results using verbal techniques.The results obtained from this study provide new insights into art therapy using visual arts to improve the behavior of children with autism. Therapy using elements of visual arts such as lines, shapes, forms, colors, and textures is explored. Family factors significantly influence the art therapy process through painting, using expression as a medium for improving the behavior of children with autism.